A multicentre, prospective cohort study comparing two endoscopic procedures for the treatment of gastric muscularis propria lesions - Zhaohui Liu; Xiangyu Wang; Genhua Yang; Jiefeng Li; Yongsheng Lu; Dayong Sun; Ruinuan Wu (Scientific Reports)
Abstract To date, no prospective study has been conducted to compare the safety and effectiveness of endoscopic snare resection with an elastic band (ESR-EB) and endoscopic snare resection with a transparent cap (ESR-C) for treating gastric muscularis propria lesions. We aimed to compare the safety and effectiveness of ESR-EB with those of ESR-C for gastric muscularis propria lesions less than 10 mm in diameter. A total of 64 patients were enrolled prospectively from May 2023 to November 2023 at Shenzhen Hospital of Southern Medical University, the First Affiliated Hospital of Shantou University, and the People’s Hospital of Zhongshan City. The study compared clinical characteristics, tumour features, and surgical outcomes between the two groups. Of 64 patients, 29 underwent ESR-C, and 35 underwent ESR-EB. There were no differences in age, gender, location, tumour size, growth pattern, resection time, histology diagnosis, or follow-up time (P > 0.05). Complete resection was achieved in all the patients. The operation time was significantly greater in the ESR-C group than in the ESR-EB group (41.31 ± 9.87 min vs. 26.26 ± 10.32 min, P = 0.000). In the ESR-C cohort, 21 patients (72.41%) had perforation, and 1 patient (3.45%) had bleeding. In the ESR-EB group, 7 patients (20.00%) had perforation. The complication rate varied significantly between the two groups (P = 0.000). No recurrence or metastasis was observed in either group during the follow-up period. Both ESR-C and ESR-EB achieved a 100% complete resection rate for gastric muscularis propria lesions less than 10 mm in diameter.ESR-EB had the potential to reduce the operation time and lower the occurrence of complications. Chinese Clinical Trial Registry Identifier ChiCTR2300072856.